WAYS TO INCREASE INVESTMENT ACTIVITY IN SMALL INDUSTRIAL ZONES OF UZBEKISTAN (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2026)
This article analyzes the development process of small industrial zones (SIZs) in the Republic of Uzbekistan, the level of investment activity within them, and mechanisms for its enhancement. The importance of small industrial zones in ensuring regional economic balance is discussed, and recommendations are developed based on state policy and international experience.